Adolescent Mentoring on Reproductive Health in Bulukunyi Village, Polongbangkeng Selatan District, Takalar Regency - Ruqaiyah Ruqaiyah; Fatmawati Amir; Ayatullah Harun; Fauziah Botutihe; Alamsyah Alamsyah (SWAGATI : Journal of Community Service, 2025)
Adolescents are in a transitional period from childhood to adulthood, making them vulnerable to reproductive health problems such as early marriage, sexually transmitted infections (STIs), and sexual abuse due to limited knowledge and social norms that restrict open discussion. This community service program aimed to improve adolescent girls' knowledge of reproductive health indicators—including understanding of reproductive organs, puberty, menstruation, early marriage risks, and STI prevention—in Bulukunyi Village, Polongbangkeng Selatan District, Takalar Regency. The activity was conducted on May 5–9, 2025, involving 20 adolescent girls as participants. Methods consisted of health education through lectures and question-and-answer sessions supported by leaflets, along with blood pressure, blood glucose, and cholesterol screening for the broader community. Pre- and post-test assessments were used to evaluate knowledge improvement. Results showed a significant increase: before the intervention, only 25% of participants had adequate knowledge of reproductive health indicators, which increased to 78% after the mentoring program. The program received strong support from local government officials, community leaders, and health workers. These findings confirm that structured health education through community mentoring is effective in improving reproductive health literacy among adolescent girls in rural areas